Theology As A Science And Ascience: An Answer To Scientists And Warning To Theologians - Stevri Penti Novri Indra Lumintang (STTRII, 2021)
Doubting theological science and limiting the primacy of theology has been a subject of debate among scientists and theologians for centuries. The study aims to answer scientists who doubt theology as a science and warn theologians who only recognize theology as science but do not recognize theology as ascience. To achieve this goal, researchers use content analysis methods. The results found that, on the one hand, theology is science essentially, not because of the recognition of theologians, but because of its understanding, characteristics, activities, and dimensions as a science. On the other hand, in accordance with its nature, theology is ascience because of its understanding and presupposition, position, adequacy, certainty, and superiority over science. These findings confirm that theology is indeed the queen of all science. If theology is recognized as science and ascience, scientists and theologians will realize knowledge and life that is entirely integrative.